Desertification of the Gwarkhola River: A Study of Ecological Ethics - Pokhrel, Tej Prasad (Haimaprabha, 2025)
This research paper tries to explore ruthless human behaviour over nature such as over excavation of river based materials. Further it investigates our recklessness and indulgence in fulfilling present needs. It tends to remind our moral duty on ecology. Good utilization of the Gwarkhola River could be milestone for economic development and environmental health. Not only agriculture has been declined but also environment has been affected. It applies mixed method.  Theory of sustainability and concept of Anthropocene are methodological framework to assess ecological ethics. Gwarkhola once used to provide sufficient water for irrigation. It was the source to cool riverbank. Nowadays, it has no water except during the rainy season. Almost no one bothers to think about its present condition. Overconsumption of natural resources create environmental problems. In the same way, Gwarkhola’s desertification may cause climate change problem even though in a small scale. Political leaders and stakeholders are failing to preserve it. Some powerful people having political approach are making money by selling its sand, concrete and stone. They are exploiting it. This process directly affects local residents but no one has raised this issue strongly yet. Results of this paper are that selfish human activities show how much irresponsible and unethical towards nature we are. In the name of sudden economic prosperity, we are losing long term economic and ecological prosperity.  The degradation of the Gwarkhola River is due to the ignorance, indifference and reluctance to preserve it. This justifies that we are morally debased. It is necessary to realize our duty and responsibility towards nature.